Multiscale modeling of the cellular uptake of C6 peptide-siRNA complexes. (June 2022) - Purijjala, P.W.C.M.; Rathnayake, P.V.G.M.; Kumara, B.T.; Gunathunge, B.C.M.; Ranasinghe, R.A.A.P.; Karunaratne, D.N.; Ranatunga, R.J.K.U.
Abstract: In gene therapy utilising short interfering RNA (siRNA), delivery of the siRNA therapeutics to the target site is a major obstacle, due to low cellular uptake. Efficient delivery systems such as cell penetrating peptides (CPPs) are in the forefront for the development of efficient, safe, non-viral gene delivery. The C6 peptide series are a class of synthetic CPPs, developed specifically for the delivery of siRNA. This series of peptides are derivatives of the original C6 peptide, modified to increase cellular uptake and efficiency. In this study, multiscaled computational simulations of these peptides were performed in aqueous media, interrogating the relationship between the structure and behaviour. All atom molecular dynamic (MD) simulation results show that all CPPs show stable α-helical amphipathic secondary structures. Furthermore, docking calculations indicate that the C6 peptides can fit into the major groove of the siRNA double-helix, and once filled, could bind randomly along the minor grooves and to other, previously bound peptides. Coarse grained MD simulations were also used to generate free energy profiles for the dimerization of peptides, and binding of the peptide to siRNA. Simulation results confirm that all peptides favour binding to siRNA, they however, also favour dimerization. This affinity for aggregation may trigger the formation of larger complexes with siRNA and enhance the cellular uptake. These results indicate the capacity of C6 peptides as efficient delivery vehicles. As expected the amino acid sequence plays a crucial role in the helicity, peptide self-assembly, interaction of peptide with cell membrane and formation of stable siRNA-CPP complex. Graphical Abstract: ga1 Highlights: C6 peptides can mediate delivery of siRNA to cells. Multiscale simulations are needed to study processes. C6 peptides can bind with siRNA, upto ratios past 30:1. C6 also can adsorb onto DOPC, and other peptides. Peptide-siRNA complexation and uptake show some correlation.